ALWAYS DAY ONE : HOW THE TECH TITANS PLAN TO STAY ON TOP FOREVER - Kantrowitz, Alex (New York : Portfolio/Penguin, 2020)
"An acclaimed tech reporter reveals the inner workings of the most powerful companies in the world, taking you behind the scenes with Amazon's Jeff Bezos, Facebook's Mark Zuckerberg, Google's Sundar Pichai, and Microsoft's Satya Nadella. At Amazon, "Day One" is code for working inventively and urgently, as if it were the first day of your startup. Day Two is, in Bezos's own words, is "stasis, followed by irrelevance, followed by excruciating, painful decline, followed by death." Amazon and its fellow tech giants are under fire for their size and power, but there's more to their story than anti-competitive practices and tax avoidance. These companies have kept ahead of the competition by embracing a new leadership model, one built for an age where companies can spin up new products and services at record speed. On the inside, these tech giants operate nothing like the corporate giants of the past -- like Exxon and GM -- which built core advantages and did everything they could to defend them. For these new goliaths, it's always day one. They are in a constant state of reinvention despite their massive size, understanding that once you become obsessed with the past, you will miss the future. Always Day One takes you deep inside these companies, revealing the uncommon cultures and leadership practices that have kept them from being picked apart by smaller, nimbler competitors. It details how their CEOs will do away with any obstacle blocking the free flow of ideas within their companies, how they're creating systems to bring the best of these ideas to life, and how they're using advanced workplace technology to make it all possible. Kantrowitz reveals a new model propelling their dominance at a stage when most big companies begin to decline. And he shows the way forward for anyone who wants to compete with -- and beat -- the existing tech giants"
Includes bibliographical references and index.
Keywords: High technology industries -- Management -- Case studies; Internet industry -- Management -- Case studies; High technology industries -- Management; Performance -- Psychological aspects